Clause of death - Barrett, Lorna (Barrett, Lorna. Booktown mystery, 2022)
"Bookstore owner Tricia Miles tries to open a new chapter in life, but murder mars the pages in the latest entry to Lorna Barrett's New York Times bestselling Booktown series. Tricia Miles and her sister, Angelica, are the co-presidents of the Stoneham Chamber of Commerce. Things are changing in the booktown, and some merchants would say not for the better. They grumble that too many non-book-related stores are moving into the village, taking up the most visible storefronts on Main Street, diluting the "Booktown" moniker. Of course, the members with other businesses, like the latest, The Bee's Knees, are fine with other businesses moving in. No matter what side of the argument they're on, all the business owners agree on one thing: Tricia and Angelica are to blame. Still, it's a pretty typical day in the life of a small-town Chamber of Commerce until one of the disgruntled bookstore owners is killed-Eli Meier from The Inner Light Bookstore, the most vocal of the Chamber complainers. He sold religious and other spiritual books, but also stocked books on wild conspiracy theories and sold incense, crystals, etc. Eli had never been a member of the Chamber until Angelica recently convinced him to join. He hit on her and she, having good taste, turned him down. He hounded (but not stalked) her, and some might think that was a motive for murder. Stoneham's new police chief is an old friend of Tricia's, but that doesn't mean he's going to go easy on her sister. One might even say that he's going to throw the book at her"--